2018
DOI: 10.1155/2018/9856851
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Suspension Containing Nanodiamonds on the Morphology of the Tooth Tissue Surface in Atomic Force Microscope Observations

Abstract: Reduced friction and wear of materials after the use of the carbon nanomaterials including nanodiamonds (NDs) have been confirmed by several studies in material engineering. Mechanical cleaning of the tooth surface by brush bristles should leave as little tissue roughened as possible. Higher surface roughness increases the tissue's wear and encourages the redeposition of the bacteria and the colouring agents present in the diet. Therefore, we evaluated the tooth tissues' surface's morphological changes after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Various techniques have been published in the literature to quantify the abrasivity of toothpaste. 14,20,30 In this study, AFM was used to quantitatively and qualitatively measure the abrasivity of EB@TiO 2 . The mean roughness values (R a ) attained were used for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various techniques have been published in the literature to quantify the abrasivity of toothpaste. 14,20,30 In this study, AFM was used to quantitatively and qualitatively measure the abrasivity of EB@TiO 2 . The mean roughness values (R a ) attained were used for statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Another useful device, like the profilometry, is the atomic force microscope (AFM) that has attracted increasing in interest in dental hard tissue studies. [19][20][21] AFM is applied widely, obtaining quantitative (roughness value) and qualitative (3D images) dental tissue analysis simultaneously at a very small scale, thereby not only offering a clear perception of the treatments and development of oral disease but also the coating of biomedical devices. 22,23 This study is aimed at evaluating the abrasivity of new toothpaste formulation containing titanium dioxide (EB@TiO 2 ) and modified eggshell powder in comparison with commercially available toothpastes using AFM.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon can lead to increased tissue wear and redeposition of the bacteria. Studies have shown that correct use of a soft-tufted toothbrush in combination with a nanodiamond suspension for oral hygiene applications can provide a protective effect on the enamel and the dentine surfaces, making them smoother, so it is harder for bacteria to adhere [43].…”
Section: Wear Protection Functionmentioning
confidence: 99%
“…At the molecular level, nanodiamond particles inhibit the gene expression responsible for oxidative stress and carcinogenesis [54] and they induce apoptosis in human endothelial cells [55]. A positive effect of diamond nanoparticles in contact with the dental tissue is also observed [56]. The toxicity of carbonbased nanomaterials, mainly graphene, carbon nanotubes and fullerenes on human and animal cells, and antibacterial activity are widely commented on in the literature.…”
Section: Introductionmentioning
confidence: 99%